IMMU-57. SEQUENTIAL TWO-RECEPTOR PRIMING CAR SYSTEM TO OVERCOME HETEROGENEOUS ANTIGEN EXPRESSION. (5th November 2018) - Watchmaker, Payal; Choe, Joseph; Carrera, Diego; Downey, Kira; Shahin, Maryam; Roybal, Kole; Lim, Wendell; Okada, Hideho
Abstract: Heterogeneous expression of target antigens can allow tumor escape from chimeric antigen receptor-transduced T-cell (CART) therapy targeting a single antigen. While epidermal growth factor receptor (EGFR)vIII represents a glioblastoma (GBM)-specific antigen, its expression is heterogeneous within the tumor. On the other hand, most other antigens expressed more uniformly in GBMs are non-mutated, glioma-associated antigens (GAAs), such as EphA2. Although these GAAs are not expressed in the normal brain, they are expressed at low levels in other normal organs. As a way to safely target GAAs in the tumor without attacking normal cells expressing the same GAAs outside of the brain, we adapted a novel synthetic Notch (synNotch) receptor system, and established a "prime and kill" sequential two-receptor CAR circuit: the first is a transcriptional CAR against EGFRvIII, and the second is a CAR against a GAA (e.g. EphA2). When the first CAR binds to EGFRvIII, it induces the expression of the second CAR. While the first CAR does not trigger the cytotoxic function itself, the second CAR mediates the cytotoxicity upon recognition of the target GAA. We have validated this system in vitro using the mixture of U87 GBM cells and those transduced with EGFRvIII. SynNotch CART effectively lysed both EGFRvIII+ and EGFRvIII-negative U87 cells when they are mixed, but never lysed EGFRvIII-negative cells in the absence of EGFRvIII+ cells. In immunocompromised mice bearing intracranial U87-EGFRvIII+/- tumors, intravenous infusion of synNotch CART resulted in long-term (over 60 days) survival and eradication of the heterogenous tumor in 5 of 8 mice. Furthermore, when mice also bear subcutaneous, EGFRvIII-negative U87 tumors along with the intracranial U87-EGFRvIII+/- tumors, synNotch CART did not affect the subcutaneous tumor, indicating the local but not systemic effects of synNotch CART. These data provide a strong basis for developing synNotch CART therapy for GBM.